Optical sectioning and high resolution visualization of trabecular meshwork using Bessel beam assisted light sheet fluorescence microscopy. Issue 12 (2nd September 2019) - Suchand Sandeep, C. S.; Sarangapani, Sreelatha; Hong, Xun J. J.; Aung, Tin; Baskaran, Mani; Murukeshan, Vadakke M.
Abstract: Glaucoma, one of the leading causes of blindness, is an eye disease caused by irregularities in the ocular aqueous outflow system causing an elevated intraocular pressure. High resolution imaging of the aqueous outflow system comprising trabecular meshwork is immensely valuable to vision analysts and clinicians in comprehending the disease state for the efficacious analysis and treatment of glaucoma. Currently available ocular imaging devices are unable to deliver high resolution images for the visualization of the trabecular meshwork. A method to obtain high resolution (sub‐micrometer) images of the trabecular meshwork using Bessel‐Gauss beam scanned light sheet fluorescence microscopy is presented and the optical sectioning capability of this technique to obtain three‐dimensional volumetric images of the trabecular meshwork of an intact eye without any physical dissection is demonstrated. Figure: Three‐dimensional visualization of trabecular meshwork of porcine eye . Abstract : Glaucoma, also known as the silent thief of sight, is a disease usually associated with elevated intraocular pressure which causes damage to the optic nerve and eventually results in irreversible loss of vision. One key challenge in the intervention and treatment of glaucoma lies in the ability to visualize the aqueous outflow system of the eye in high resolution. This study reports a method to realize high resolution three‐dimensional visualization of the aqueous outflow system of the eye, in particular the trabecular meshwork.